Does the Urinary Calcium/Citrate Ratio Help in the Diagnosis of Children at Risk of Urolithiasis? - Utku Dönger; Aysun Çaltık Yılmaz; Caner İncekaş; Kaan Gülleroğlu; Esra Baskın (Güncel Pediatri)
Introduction: Citrate acts as a stone inhibitor, reducing urinary concentration and thus stone formation. It accounts for 50% of the inhibitory activity against calcium phosphate precipitation in urine. The urinary calcium-citrate ratio is a proposed method for assessing urolithiasis risk. Evaluating high urinary calcium alongside citrate may be more informative than high calcium alone. This study aims to highlight the significance of the calcium/citrate ratio as an additional parameter in assessing urolithiasis risk in children. Materials and Methods: In this study, patients aged 0-18 years with a prediagnosis of urolithiasis who presented to the Pediatric Nephrology outpatient clinic of Başkent University Ankara Hospital between January 2012 and January 2023 were retrospectively analysed. Patients with calcium and citrate levels in spot or 24-hour urine and urinary system USG at initial presentation were included in the study. Statistical analyses were performed using SPSS version 25.0 software. This study was conducted in accordance with the principles of the Declaration of Helsinki. Approval was obtained from the Başkent University Ethics Committee. Results: In this study, 198 patients (60.9%) had stones detected by the first ultrasound, while 127 (39.1%) did not. We compared urinary metabolic parameters between the two groups. The mean spot urine calcium/citrate (ca/cit) ratio was 0.33±0.49 mg/dl (median 0.18) for patients without stones, and 0.48±0.55 mg/dl (median 0.31) for those with stones. The 24-hour urine ca/cit ratio was 0.38±0.96 mg/mg (median 0.23) for patients without stones and 0.58±1.09 mg/mg (median 0.32) for those with stones. We aimed to establish a threshold for predicting stones based on these measurements, finding the optimal cut-off point for spot urine ca/cit ratio to be 0.23, with the highest sensitivity and selectivity. Conclusion: Not only hypercalciuria or hypocitraturia alone,but also insufficient citrate for a given urinary calcium concentration may be an important risk factor for stone formation in childhood.This is because stone formation is relatively a joint product of hypocitraturia and hypercalciuria. A calcium to citrate ratio greater than 0.23 in spot urine may be significant in predicting stone formation.